Development of Art Therapy in Chile - Serrano Morales, Paula (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2008)
This article presents a touch of what has been the development of Art Therapy in Chile. Bringing the reader to the different processes and difficulties involved in being precursors of a different discipline, in a country that needs new materials and professionals. We briefly closer since its inception, how emerged from the hands of professionals who gave importance to the visual images as a therapeutic agent. We also talk about what has been its development at the university level, as there is a need to regulate the practice and teaching through the creation of an association grouping all Chileans Art Therapists. And finally, what are the areas in which action has been inserted Art Therapy, as a way to benefit the Chilean society.
Keywords: Art Therapy in Chile; Visual images as a therapeutic agent; Chileans Art Therapists Chilean society